Job Satisfaction Analysis: The Influence Of Work Engagement, Person Environment Fit, and Work Life Balance On Job Satisfaction of Employees of PT. Inka Multi Solution Trading - Naimatu Saniati Rodhiya; Naning Kristiyana; Siti Chamidah (Dinasti Publisher, 2024)
This study aims to test and analyze the effect of Work Engagement, Person Environment Fit, and Work Life Balance on Job Satisfaction in employees of PT INKA Multi Solusi Trading. This study uses a quantitative approach and explanatory research. The population in this study were employees of PT INKA Multi Solution Trading (IMST) with a total of 71 people. The data analysis technique used is multiple linear regression using the IBM SPSS (Statistical Package for Social Science) program version 25. The results showed that there was a direct and proven significant effect of Work Engagement and Work Life Balance on Job Satisfaction. However, the variable Person Environment Fit has no significant effect on Job Satisfaction. Main Findings: Work Engagement and Work Life Balance have a direct and significant influence on Job Satisfaction; Person Environment Fit does not have a significant influence on Job Satisfaction. The findings of this study indicate that Work Engagement and Work Life Balance are important factors that influence Job Satisfaction of PT INKA Multi Solusi Trading employees. Companies need to focus on efforts to improve Work Engagement and Work Life Balance of their employees to increase Job Satisfaction and ultimately improve company performance.